2021
DOI: 10.3390/diagnostics11050877
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Micro-Elimination beyond Prison Walls: Navigator-Assisted Test-and-Treat Strategy for Subjects Serving Non-Custodial Sentences

Abstract: Background and Aims: The Spanish prison population includes two groups: people in prison and those who are serving non-custodial sentences. The latter has not yet been studied. This study aims to describe this population and the results of a test-and-treat strategy for hepatitis C including a holistic health assessment. Method: This prospective study included all subjects serving non-custodial sentences at the Center for Social Integration. It was assisted by the medical team, a navigator, and a systematic scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Spain started a pilot program to detect and treat HCV in prisons in 2016. The results of this study showed that a sustained viral response was achieved in greater than 95% of treated patients [ 7 ], and this result is consistent with our data. Toxicity and therapeutic abandonment were exceptional [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Spain started a pilot program to detect and treat HCV in prisons in 2016. The results of this study showed that a sustained viral response was achieved in greater than 95% of treated patients [ 7 ], and this result is consistent with our data. Toxicity and therapeutic abandonment were exceptional [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…16 However, in Spain, one model of care to screen and treat all HCV-RNA positive patients through telemedicine has shown promising HCV elimination results, with cure rates of 97%, 17 and another which targeted those serving noncustodial sentences in Spain had good success with a novel microelimination approach. 18 In addition, using telemedicine to engage incarcerated persons has been reported as cost saving. 19 In the United Kingdom, a recent study has reported promising testing and treatment uptake among incarcerated persons using a rapid screening and treatment model.…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed and OVID Medline for studies published in English language using the search terms hepatitis C OR viral hepatitis AND probation OR parole OR community correction∗ and found four studies which evaluated viral hepatitis testing in community corrections and linkage to onsite (n = 1) or external (n = 3) assessment and treatment services ( Table 1 ). Onsite assessment and treatment was evaluated by Cabezas and colleagues 24 who reported that among 548 people who received point-of-care finger-prick testing at a single community corrections site in Spain, 16 (3%) were hepatitis C RNA positive, of whom 13 (81%) commenced treatment. In Pawtucket, Rhode Island, Jacka et al.…”
Section: Hepatitis Care In Community Corrections: a Novel Settingmentioning
confidence: 99%